Job mobility, peer effects, and research productivity in economics - Thomas Bolli; Jörg Schläpfer (ETH Zurich, KOF Swiss Economic Institute, 2013)
Analysing a comprehensive panel dataset of economists working at Austrian, German, and Swiss universities, we investigate how the local environment influences a scientist's research productivity. The research environment varies if a scientist joins another department or if the characteristics of his colleagues change. We find no influence of the research environment on the average researcher's productivity, if we control for individual characteristics. This result indicates that with today's communication technologies spillovers are not bounded locally.
Keywords: I23; J62; 330; University; economics; productivity; mobility; peer effects; bibliometrics